Mechanisms in Cognitive Psychology: What Are the Operations? - Bechtel, William (Philosophy of Science, 2008)
Cognitive psychologists, like biologists, frequently describe mechanisms when explaining phenomena. Unlike biologists, who can often trace material transformations to identify operations, psychologists face a more daunting task in identifying operations that transform information. Behavior provides little guidance as to the nature of the operations involved. While not itself revealing the operations, identification of brain areas involved in psychological mechanisms can help constrain attempts to characterize the operations. In current memory research, evidence that the same brain areas are involved in what are often taken to be different memory phenomena or in other cognitive phenomena is playing such a heuristic function.